Constitutional Law around the globe: judicial review in Canada and the “leave to appeal” to the Supreme Court - Luiz Henrique Diniz Araujo (Revista de Investigações Constitucionais)
This paper exploring the leave to appeal in Canadian Constitutional Law is the third of the series “Constitutional Law Around the Globe”. This section of the series focuses on “Judicial Review and the Filters to Access Supreme and Constitutional Courts”. The first paper in the row, published in the year 2019, analyzed the Constitutionality Priority Question (Question Prioritaire de Constitutionnalité – QPC) in France. In a second paper, we analyzed the writ of certiorari of the U.S. Supreme Court. In this third text, we approach the process according to which the Supreme Court of Canada picks cases from hundreds that reach it every year and the strategies that the Court adopts to select these cases. The paper focuses specifically on Section 41(1) of the Supreme Court Act (amended in 1975), the leave to appeal and their operation in practice.